The 12th June 2017 Mw = 6.3 Lesvos earthquake from detailed seismological observations - Papadimitriou, P.; Kassaras, I.; Kaviris, G.; G.-A. Tselentis; Voulgaris, N.; Lekkas, E.; G. Chouliaras; C. Evangelidis; K. Pavlou; V. Kapetanidis; A. Karakonstantis; D. Kazantzidou-Firtinidou; et al. (Journal of Geodynamics, 2018)
A major earthquake (Mwö=ö6.3) occurred on the 12th of June 2017 (12:28 GMT) offshore, south of the SE coast of Lesvos Island, at a depth of 13ökm, in an area characterized by normal faulting with an important strike-slip component in certain cases. Over 900 events of the sequence between 12 and 30 June 2017 were manually analyzed and located, employing an optimized local velocity model. Double-difference relocation revealed seven spatially separated groups of events, forming two linear branches, roughly aligned N130°E, compatible with the strike of known mapped faults along the southern coast of Lesvos Island. Spatiotemporal analysis indicated gradual migration of seismicity towards NW and SE from the margins of the main rupture, while a strong secondary sequence at a separate fault patch SE of the mainshock, oriented NW-SE, was triggered by the largest aftershock (Mwö=ö5.2) that occurred on 17 June. The focal mechanisms of the mainshock (φö=ö122°, δö=ö40° and λö=ö−83°) and of the major aftershocks were determined using regional moment tensor inversion. In most cases normal faulting was revealed with the fault plane oriented in a NW-SE direction, dipping SW, with the exception of the largest aftershock that was characterized by strike-slip faulting. Stress inversion revealed a complex stress field south of Lesvos, related both to normal, in an approximate E-W direction, and strike-slip faulting. All aftershocks outside the main rupture, where gradual seismicity migration was observed, are located within the positive lobes of static stress transfer determined by applying the Coulomb criterion for the mainshock. Stress loading on optimal faults under a strike-slip regime explains the occurrence of the largest aftershock and the seismicity that was triggered at the eastern patch of the rupture zone.
Keywords: Aftershock relocation; Coulomb stress; Focal mechanism; North Aegean; Seismotectonics; Stress inversion